2023
DOI: 10.1186/s13148-023-01468-y
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and cardiovascular disease in humans: a systematic review and database of known CpG methylation sites

Abstract: Background Cardiovascular disease (CVD) is the leading cause of death worldwide and considered one of the most environmentally driven diseases. The role of DNA methylation in response to the individual exposure for the development and progression of CVD is still poorly understood and a synthesis of the evidence is lacking. Results A systematic review of articles examining measurements of DNA cytosine methylation in CVD was conducted in accordance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…Two CpG sites were referenced in at least 6 publications and were related to vascular disease and epigenetic age (cg01656216 near ZNF438 ) and coronary heart disease, myocardial infarction, smoking, and air pollution (cg03636183 near F2RL3 ). 13 These results highlight the potential of DNA methylation as a rich source of biomarkers for cardiovascular diseases.…”
Section: Epigenetic Mechanisms and Cardiometabolic Diseasesmentioning
confidence: 87%
“…Two CpG sites were referenced in at least 6 publications and were related to vascular disease and epigenetic age (cg01656216 near ZNF438 ) and coronary heart disease, myocardial infarction, smoking, and air pollution (cg03636183 near F2RL3 ). 13 These results highlight the potential of DNA methylation as a rich source of biomarkers for cardiovascular diseases.…”
Section: Epigenetic Mechanisms and Cardiometabolic Diseasesmentioning
confidence: 87%
“…DNA methylation is involved in cellular progression, including tumorigenesis, cell development, metastasis, apoptosis, cell cycle, and growth [ 29 ]. Increasing evidence indicates that DNA methylation influences the occurrence and development of human diseases [ 30 , 31 ]. However, the effects and molecular mechanisms of DNA methylation in hypertrophy remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found DNA methylation sites associated with CVD and PM 2.5 . CpG sites cgo1656216 (near ZNF438 ) and cgo3636183 (near F2RL3 ) were significantly associated with CVD and air pollution ( Krolevets et al, 2023 ). Similarly, some clinical trials have shown the association between DNA methylation, CVD, and PM.…”
Section: Pm-induced Dna and Histone Modifications Within The Context ...mentioning
confidence: 99%